Creatinine concentrations of accumulated intrauterine fluid to confirm the clinical diagnosis of urometra in mares. (25th March 2017) - Schnobrich, M. R.; Gordon, D. L.; Scoggin, C. F.; Bradecamp, E. A.; Canisso, I. F.
Abstract : Urine pooling, as a persistent condition, is a cause of infertility in mares due to endometrial inflammation and sperm toxicity. Identification of urometra can be challenging in mares presenting with the condition intermittently, or when urine flows into the uterus but is undetectable in the vagina. Currently, there are no reported objective methods to confirm the clinical diagnosis of urine contamination in intrauterine‐fluid accumulations. Since creatinine is present in high concentrations in urine and does not diffuse across cell membranes, creatinine concentration should be increased in mares with urometra, but negligible in normal and mares with intrauterine fluid accumulation (non‐urometra cases). To test this hypothesis, creatinine concentrations of intrauterine fluid were measured in mares with a clinical diagnosis of urine accumulation (n=9) or intrauterine fluid containing no urine (n=10). Results showed that creatinine concentrations (mg/dl) were significantly higher in mares that had a clinical diagnosis of urometra (42.8±12.6, range 4.1–109.2) compared with those that did not (0.38±0.1, range 0–0.9). Also, two mares after urethral extension surgery demonstrated a remarkable reduction in creatinine concentrations. This study highlights an undocumented approach to confirm a clinical diagnosis of urometra in mares; the authors anticipate that testing for creatinine in the uterine fluid of mares may become a standard tool for identifying urometra in mares and confirming the success of urogenital surgeries.